Exploring asset-based community development in intangible cultural heritage management - Trixie Marjorie Tangit; Jurry Foo; Badariah Saibeh (Academics Inspired Network, 2022)
Intangible cultural heritage is important to any community and a community-driven approach encourages communities to avoid becoming overly dependent on external agencies that are held responsible to solve the problems of the community. Thus, an asset-based community development (ABCD) approach may be a better option as one of the positive aspects of ABCD is the focus on local resources as assets, specifically in identifying existing human resources and evaluating their sustainability. The authors propose that the recently launched TABIK, a culture and innovation theme park in Kundasang, Ranau district, in Sabah, Malaysia, meets this criterion of valuing their own community members as resources or assets.